Effect of a pathway bundle on length of stay. Issue 7 (22nd June 2009) - Sloan, J; Chatterjee, K; Sloan, T; Holland, G; Waters, M; Ewins, D; Laundy, N
Abstract : Background: Pathways to guide clinical care are well accepted and used in many emergency departments. We wanted to introduce a number ("bundle") over a short space of time and involve the whole patient stay in the pathway. It was hypothesised that a more efficient process would result with an overall reduction in length of stay (LoS). Methods: A "bundle" of 14 evidence-based pathways of care was introduced into a medium-sized district general hospital (DGH) in late 2006/early 2007. These pathways covered emergency department care and acute medical care for a period of up to 48 h. A total of 8184 acute emergency admission episodes were audited, 3852 in the 8 months before introduction of the new pathways and 4332 in the 8 months after their introduction. Results: The overall effect of introducting the pathway bundle had a trend towards reduction in LoS by 0.2 days (95% CI −0.2 to 0.5), but this was not statistically significant (p>0.1). However, in those patients with ⩽2 diagnoses, the introduction of the pathway bundle had an independent effect in reducing LoS by 0.4 days (95% CI 0.04 to 0.7, p<0.01). In patients with ⩽2 diagnoses (63.0% of all pre-pathway cases and 63.4% of all post-pathway cases), the reduction in LoS equates to a saving of 2154 (CI 215 to 3769) bed days per annum or 5.9 (CI 0.6 to 10.3) beds saved each day. This reduced LoS represents an improvement of 2.5% (CI 0.25% to 4.38%) in medical bed usage. As this benefit occurs in the uncomplicated group of patients without multiple co-morbidities, such pathways would have the most effect in the type of patients who may be looked after by an emergency or acute physician. They are much less likely to be effective in those who require specialist intervention due to a more complicated presentation and possibly those with multiple co-morbidities. Conclusion: The introduction of a bundle of evidence-based care pathways can modestly reduce LoS for certain types of acute medical patients in a DGH setting.